2014
DOI: 10.1177/2150135113516370
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatment of Common Arterial Trunk in Patients Beyond the First Year of Life

Abstract: Complete repair of common arterial trunk in patients older than one year of age is feasible in appropriately selected cases. Preoperative cardiac catheterization to assess reactivity of the pulmonary vascular bed is important as are appropriate strategies for postoperative management. Together, these elements make it possible to achieve primary repair with excellent outcomes despite late presentation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 29 publications
2
7
0
Order By: Relevance
“…Oversizing conduits (z valve: 2.3 ± 1.3) were used in high-pressure system to prolong the conduit life. This was also consistent with data reported by Fiore and associates [ 22 ], as well as others [ 13 , 23 ]. Furthermore, Joyce and his associates [ 24 ] reported that smaller conduit size was a significant factor associated with early conduit reoperation.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Oversizing conduits (z valve: 2.3 ± 1.3) were used in high-pressure system to prolong the conduit life. This was also consistent with data reported by Fiore and associates [ 22 ], as well as others [ 13 , 23 ]. Furthermore, Joyce and his associates [ 24 ] reported that smaller conduit size was a significant factor associated with early conduit reoperation.…”
Section: Discussionsupporting
confidence: 94%
“…The PVRi of 6–8 wood units.m 2 was widely accepted as a cut-off for operability in children with large left to right shunts [ 12 ]. Our patients’ PVRi were similar to those seen in one study from Turkey [ 13 ] which reported surgical repair experience with 7 patients with a mean PVRi of 9.04 ± 4.2 wood units.m 2 beyond the first year of life. However, assessing operability only on the basis of cardiac catheterization might be misleading.…”
Section: Discussionsupporting
confidence: 86%
“…13 Some teams remain in favour of the systematic preoperative haemodynamic catheterisation, in particular in children older than 1 year. 14,15 For others, on the other hand, the catheterisation with calculation of pulmonary vascular resistances does not have preoperative benefit when obvious clinical signs of a significant left-to-right shunt persist and does not have to be systematically done any more, even after 1 year of age. In our series, 78% of the treated children (26/33) were more than 1 year old at the point of surgery, and only 14 out of 26 had a preoperative exploratory catheterisation.…”
Section: Discussionmentioning
confidence: 99%
“…Since PH is an important cause of morbidity and mortality in patients with TA beyond three months of age, [3] we attempted to initiate inhaled nitric oxide upon weaning from CPB. Nitric oxide was given between 10 to 20 ppm and continued 24 hours postoperatively.…”
Section: Case Reportmentioning
confidence: 99%
“…Without surgical treatment, 80% of patients die within the first year of life, mostly during early infancy. [2,3] The first successful correction of truncus arteriosus was performed in 1965 by McGoon et al [4] Since then, there have been many advances in the surgical management with an evident trend to perform primary repair in early infancy, thereby, avoiding the complications of pulmonary hypertension (PH). Although timing of TA repair is advocated by most surgeons during the first three months of life, [2] advanced anti-PH treatment modalities and increased surgical experiences encourage us to perform these challenging operations in all age groups.…”
mentioning
confidence: 99%